Construction reliability : safety, variability and sustainability - Baroth, Julien; Schoefs, Franck; Breysse, D. (London : ISTE ; Hoboken, N.J. : John Wiley, 2011)
'This book provides answers to the following problems: how to identify the most probable critical failures; how to describe and use data-concerning materials that are either heterogeneous, time-variant, or space-variant; how to quantify the reliability and lifetime of a system; how to use feedback information to actualize reliability results; and how to optimize an inspection politic or a maintenance strategy. Numerous authors from public research centers and firms propose a synthesis of methods, both new and well-known, and offer numerous examples concerning dams, geotechnical study, and structures from nuclear and civil engineering.'--
pt. 1. Qualitative methods for evaluating the reliability of civil engineering structures -- pt. 2. Heterogeneity and variability of materials : consequences for safety and reliability -- pt. 3. Metamodels for structural reliability -- pt. 4. Methods for structural reliability over time -- pt. 5. Reliability-based maintenance optimization.
Includes bibliographical references and index.
Print version record.
Keywords: Buildings -- Reliability; Public works -- Reliability; Structural failures -- Prevention; TECHNOLOGY & ENGINEERING -- Civil -- General; Electronic books